2002
DOI: 10.1590/s0034-89102002000700004
|View full text |Cite
|
Sign up to set email alerts
|

Análise sociodemográfica da epidemia de Aids no Brasil, 1989-1997

Abstract: OBJETIVO: Descrever a evolução temporal da epidemia de Aids, no nível individual, sob a perspectiva de variáveis sociodemográficas e comportamentais, com ênfase na escolaridade. MÉTODOS: Foram analisados os casos de Aids de 20 a 69 anos de idade, notificados ao Sistema de Informação de Agravos de Notificação do Ministério da Saúde e diagnosticados entre 1989 e 1997, com diferença maior que sete dias entre as datas de óbito e de diagnóstico. Foram considerados três graus de escolaridade: "grau I" (com até 8 ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1
24

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 9 publications
(11 reference statements)
4
28
1
24
Order By: Relevance
“…Of the 828 patients investigated, 254 died (30.7%) and of these, 194 (76.4%) died during the initial attendance and 44 (17.3%) within the first 48 h of hospitalization. The average number of admittances per patient was 1.5 ± 1.4 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The number of infectious complications at death was of 2.1 ± 1.1 (0-8) and 231 (90.9%) patients presented up to three opportunistic infections at death.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 828 patients investigated, 254 died (30.7%) and of these, 194 (76.4%) died during the initial attendance and 44 (17.3%) within the first 48 h of hospitalization. The average number of admittances per patient was 1.5 ± 1.4 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The number of infectious complications at death was of 2.1 ± 1.1 (0-8) and 231 (90.9%) patients presented up to three opportunistic infections at death.…”
Section: Resultsmentioning
confidence: 99%
“…The low M:W rate obtained can be partially explained by sexual exposure as the most probable form of HIV transmission, with prominence of heterosexual behavior. The increase in heterosexual cases is a decisive factor concerning the increased female participation in the epidemic 9,11,12 . These data reflect the importance of interrupting the epidemiological chain that is occurring in our region, through preventive policies focusing on female participation in the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…A tendência de crescimento relativo da epidemia de AIDS em mulheres 2,3 , especialmente daquelas em idade reprodutiva, trouxe como consequên-cia a elevação do número de crianças infectadas pela transmissão vertical, que consiste na passagem do vírus da mãe para filho, o que pode ocorrer durante a gestação, o parto ou a lactância 4,5 .…”
Section: Introductionunclassified
“…In a historical cohort study analyzing the period from 1990 to 2003, researchers found a higher number of cases diagnosed in the southeastern and southern regions (80%), approximating the findings of this study, where we found those two regions had 84.2% of diagnosed cases. Another study stated that the low participation of other regions, especially the northern region, may reflect a delayed introduction of the AIDS epidemic into these macro-regions and problems with the surveillance system (8,(10)(11) . Although the use of secondary data presents numerous advantages, incomplete notifications hinder the knowledge of the true picture of the epidemic in Brazil.…”
Section: Discussionmentioning
confidence: 99%